Modern methods of teaching foreign languages in Uzbek education - UMIRZOKOVA, FOTIMA IRISBOYEVNA; BURIBAYEVA, SHAROFAT ABDURAXMANOVNA; NARMATOVA, AYJAN POLATOVNA; ABDUKHAPAROVA, DILAFRUZ MIRZAKHMATOVNA (The journal of contemporary issues in business and government, 2021)
The article highlights the actual problems of modernization and improving the quality of teaching English. Particular attention is paid to the characteristics of the most effective methods of teaching English in higher education. The implementation of this idea is impossible without the development and implementation of appropriate teaching technologies. High school should not be a preparation for life; high school should be life. This can be achieved through an innovative approach by creating an interactive environment. The paper discusses the features of the use of interactive teaching methods in the classroom in the English language, gives examples of them and analyzes the ways of their implementation. Particular attention is paid to the use of these technologies in the foreign language speech activity of students.